Studi Komparatif Investasi Konvensional dan Syariah di Pasar Modal - Ahmad Habib Alwi; Bibit Waluyo; Esty Apridasari (Indonesia Economic Journal, 2025)
This study aims to analyse and compare the performance of conventional and Islamic investments in the capital market. Using historical data from the conventional stock index and the Islamic stock index over a period of time, this study evaluates the differences in terms of return, risk, and volatility between the two types of investments. In addition, this study also identifies the factors that affect the performance of conventional and Islamic investments, and analyses the implications of these differences for investors. The results are expected to provide comprehensive insights for investors in making investment decisions that are in line with their risk preferences and financial principles. This study contributes to a deeper understanding of the dynamics of Islamic investment in the capital market and its comparison with conventional investment.